مستويات التعبير اللغوي عند الشاعر حافظ جميل في ديوانه نبض الوجدان - العكاش، سعد ياسين لطيف (كلية الإمارات للعلوم التربوية, 2020)
This is an attempt that we do not know the extent of its success or failure to apply the method of studying the language of literary text through several expressive levels that enable us to reveal its technical and objective aspects by following the poetic term in the text in its various semantic and aesthetic contexts, up to a holistic view that exceeds the heavy sense. This attempt avoids literary and critical studies that are based on the automatic collection of texts and the premature and costly analysis of molecules, which often leads to scattered steps that are not stranded and not contained within a framework. Here, the researcher tried to apply such a systematic mechanism in the study of the poet Hafez Jamil's book.
هذه محاولة لا ندري مدى نجاحها أو إخفاقها لتطبيق أسلوب دراسة لغة النص الأدبي من خلال مستويات تعبيرية عده تمكننا من الكشف عن جوانبه الفنية والموضوعية من خلال متابعة المفردة الشعرية في النص في سياقاتها الدلالية والجمالية المختلفة وصولا لنظرة كلية تتجاوز الحس الثقيل. إن هذه المحاولة تبتعد عن الدراسات الأدبية والنقدية التي تقوم على التجميع الآلي للنصوص والتحليل المبتسر والمتكلف للجزيئات والذي يقود في كثير من الأحيان إلى خطوات مبعثرة لا يشدها خيط ولا يضمها إطار. وحاول الباحث هنا تطبيق مثل هذه الآلية المنهجية في دراسة ديوان الشاعر حافظ جميل (نبض الوجدان).
Keywords: النصوص الادبية -- التعبير اللغوي -- جميل، حافظ، ت. 1984 م. -- الشعر العربي